A rare case of ileus caused by ileum endometriosis - Bratu, Dan (Int J Surg Case Rep, 2016)
INTRODUCTION: We report our experience involving a rare case of ileum endometriosis complicated with small bowel obstruction. PRESENTATION OF CASE: 33 years old female patient, admitted to emergency service with abdominal pain, abdominal distension, and vomiting. Abdominal X-ray showed dilated small bowel loops. Computerized tomography scan showed dilated small intestine segments excepting last ileum loop, gastric distension, enlarged ovaries. Emergency laparotomy was performed, showing acute bowel obstruction due to a stenotic tumor placed on the terminal ileum, cecum tumors, multiple tumors in Douglas pouch, multiple mesenteric enlarged lymph nodes. Right colectomy is performed with an ileo-transverso stomy placed in right hypochondrium. Postoperative evolution without complication, patient discharged after 13-days hospitalization. After hormonal treatment, she returned for a second look and ileotransverso anastomosis. DISCUSSION: Gastrointestinal involvement of endometriosis has been found in 3%–37% of menstruating women. Ileum localization is very rare (1%–7%), causing intestinal obstruction 7%–23% of cases. Intraoperative differential diagnosis is difficult, predisposing at confusion with other types of tumors. In the absence of fast microscopic exam, the tumor was considered malignant and imposed a right hemicolectomy. CONCLUSION: Intestinal obstruction due to ileum endometriosis is a rare condition, however, it should always be considered in the differential diagnosis in women of reproductive age.